Financial and Debt Management of Small Medium Enterprises for Housewives in Srowot, Kalibagor, Banyumas. - Nawalin Nazah; Dwi Winarni (Journal of Society, Community and Business Development, 2024)
The program aims to provide an understanding of the Financial and Debt Management of Small Businesses for housewives in Srowot Village, Kalibagor, Banyumas Regency. Financial and debt management are two important aspects for maintaining the financial stability of individuals, families, or small businesses run by housewives of Srowot Village. Effective financial management includes planning, budgeting, and monitoring cash flow to achieve financial goals. On the other hand, education of debt aims to provide an understanding of not making debt a lifestyle so it will not burden the financial conditions in the future, especially for consumptive purposes. With good financial management and an understanding of debt, families can manage their financial systems and balance income and expenses.